The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1964
DOI: 10.1002/jez.1401550312
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal fertilization between the domesticated rabbit and the snowshoe hare with special reference to insemination of rabbits with an equal number of hare and rabbit spermatozoa

Abstract: Previous studies have shown that when Domesticated Rabbits (Oryctolagus cuniculus) were inseminated with sperm of the Cottontail Rabbit (Sylvilagus floridanus) about 30% of the ova were fertilized (Chang and McDonough, '55; Chang, '60). When domesticated rabbits were inseminated with European Hare (Lepus europaeus) sperm practically all the ova were fertilized (Adams, '57; Chang and Adams, '62). In both cases, however, all the fertilized ova degenerated before or at the time of enlargement of the blastocysts. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1965
1965
2009
2009

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…A similar experimental series with rabbits inseminated with semen from the hare Lepus europaeus yielded blastocysts but no implantation (Adams, 1957;Chang and Adams, 1962). When rabbits were inseminated with the semen of the hare L. americanus, there were essentially the same findings (Chang et al, 1964;Chang, 1965). (See also the review by Chang and Hancock, 1967.)…”
Section: Protein Synthesis and Gene Actionmentioning
confidence: 62%
“…A similar experimental series with rabbits inseminated with semen from the hare Lepus europaeus yielded blastocysts but no implantation (Adams, 1957;Chang and Adams, 1962). When rabbits were inseminated with the semen of the hare L. americanus, there were essentially the same findings (Chang et al, 1964;Chang, 1965). (See also the review by Chang and Hancock, 1967.)…”
Section: Protein Synthesis and Gene Actionmentioning
confidence: 62%
“…In the dromedary camel, gestation length is 365-410 days (Chaudhary 2000). It is suggested that successful hybridisation between two species depends on the ability of the sperm of one species to bind to the oocyte of the other species (Chang et al 1964;Hancock and McGovern 1964;Hancock et al 1968;Allen and Short 1997). In addition, it has been determined that, in fertilised eggs, the paternal genome is essential for the normal development of extraembryonic tissue and the maternal genome is essential for some stages of embryogenesis (Barton et al 1985).…”
Section: Discussionmentioning
confidence: 99%
“…For example, high fertilization rates are achieved when inseminating female goats with ram semen, but many fewer conceptions occur when reciprocally inseminating ewes with goat semen (Hancock and McGovern 1964;Hancock et al 1968). Similarly, hybrid matings between the hare (Lepus americanos) and the rabbit (Oryotolagus cuniculus) produce high rates of fertilization when rabbits are inseminated with hare semen, whereas less than 10% of hare oocytes are fertilized by rabbit semen (Chang et al 1964). In addition, inseminating a horse mare with Jack donkey semen to produce a mule, is as fertile as the straightforward intraspecies mating between either parental species, whereas the reciprocal cross between the female donkey and the male horse is very much less fertile (Allen and Short 1997).…”
Section: Discussionmentioning
confidence: 99%